Dynamic Coefficients of Finite Length Journal Bearing. Evaluation Using a Regular Perturbation Method - Merelli, Claudio Ernesto (2019)
A set of simple expressions is deduced for static and dynamic parameters associated to hydrodynamic journal bearings (JB). The behavior of this system is governed by two dimensionless numbers, the aspect ratio, L/D, and the eccentricity ratio, η. In a previous work, we presented a regular perturbation method that extended the Ocvirk solution and successfully described isothermal JBs up to L/D and η of ∼1/2. Presently, we extend that methodology, modified using a smaller perturbation parameter, to obtain analytical expressions of the dynamic coefficients, as well as static variables like friction factor, load carrying capacity, lubricant flow rate and phase angle. The deduced expressions successfully describe the static and dynamic behavior of JBs up to L/D and η of ∼3/4.